Biometric relationships of the black-lip pearl oyster Pinctada margaritifera (Linnaeus, 1758) from the Andaman and Nicobar waters - J, Abraham K; Libini, C L; Basak, R; Madhupal, P; Kripa, V; Velayudhan, T S; Mohamed, K S; Modayil, M J (Indian Journal of Fisheries, 2011)
The black-lip pearl oyster, Pinctada margaritifera is widely distributed in Indo-Pacific region and has prime importance in the production of black pearls. In India, its natural occurrence is confined to the Andaman and Nicobar Islands. The biometric relationships between (dorso-ventral measurement [DVM] and Hinge Length [HL]; Thickness [THK] and Total Weight [TWT]) were studied from 458 oysters collected from these islands which were grouped in to 5 length classes. In all size groups, there was increase in weight with increase in length. The highest coefficient (r2=0.7828) was obtained for the animals with DVM ranging from 76 to 95 mm. The correlation coefficient ‘r’ was low for DVM-HL and slightly higher for DVM-THK. Comparisons of biometric relationships of the natural populations of the Indian pearl oysters with that of farmed oysters in other regions indicated xenomorphism in pearl oysters in Andaman and Nicobar Islands due to restricted space in natural habitats